Virginity-sparing management of hematocolpos with imperforate hymen: case report and literature review - Egbe, Thomas Obinchemti (SAGE Open Med Case Rep, 2019)
Imperforate hymen results from failure of the endoderm of the urogenital sinus to completely canalize and has an incidence of 0.01% to 0.05%. This sometimes presents as a pelvic mass that compresses the bladder causing acute urinary retention. A 13-year-old girl was referred to our department with a history of primary amenorrhea, cyclic lower abdominal pain, abdominal–pelvic mass, constipation and acute urinary retention. She had an ultrasonography misdiagnosis of a huge ovarian mass before referral to our unit. On examination, the vagina was bulging and compressing the rectum. Repeat abdominal ultrasonography confirmed the diagnosis of hematometrocolpos. She underwent X-shaped hymenotomy with a favorable outcome. Diagnosis of imperforate hymen requires high suspicion index. Virginity-sparing surgery constitutes a good treatment option for cultural and religious reasons.